2018
DOI: 10.1186/s12877-018-0962-5
|View full text |Cite
|
Sign up to set email alerts
|

“You’ve got to look after yourself, to be able to look after them” a qualitative study of the unmet needs of caregivers of community based primary health care patients

Abstract: BackgroundThere is growing reliance on unpaid caregivers to provide support to people with care needs. Integrated care approaches that aim to coordinate primary care with community care known as community based primary health care (CBPHC) has been a key policy initiative across health systems; however most attention has been paid to the needs of patients and not caregivers. The objective of this paper was to explore the unmet needs of caregivers of older adults with complex care needs receiving CBPHC.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
1
31
0
5
Order By: Relevance
“…As noted earlier, campus continuums strongly align with the WHO's expanding Age Friendly Cities movement (66) to enhance seniors' local participation and provide measures to give them opportunities to live safe, independent and digni ed lives (43,44,1). They further align with the Global Plan and Action Strategy for Aging and Health (16,67) now driving "seniors strategies" in Ontario a movement committed to action on healthy aging, developing sustainable and equitable systems and providing age-friendly integrated care over the longer-term in affordable and accessible settings (home -LTCHs) that meet the needs, rights and preferences of older populations (8,9,10) (16,67) While case study respondents highlighted many advantages to providing a broad mix of services and housing, they noted that were they to construct a campus de novo, they would be more mindful of tensions that might arise due to differences across buildings by income (e.g., market rent with balconies and/or more expensive nishes). To mitigate these tensions and address feelings of "other" sometimes experienced by lower income residents, it is suggested that new campuses engage in proactive planning to minimize the occurrences or need for these differences, provide basic service packages for all residents to engage in joint activities (e.g., congregate dining, excursions), and ensure representation from the various housing components on tenant committees.…”
Section: Campus Design and Functionsmentioning
confidence: 95%
“…As noted earlier, campus continuums strongly align with the WHO's expanding Age Friendly Cities movement (66) to enhance seniors' local participation and provide measures to give them opportunities to live safe, independent and digni ed lives (43,44,1). They further align with the Global Plan and Action Strategy for Aging and Health (16,67) now driving "seniors strategies" in Ontario a movement committed to action on healthy aging, developing sustainable and equitable systems and providing age-friendly integrated care over the longer-term in affordable and accessible settings (home -LTCHs) that meet the needs, rights and preferences of older populations (8,9,10) (16,67) While case study respondents highlighted many advantages to providing a broad mix of services and housing, they noted that were they to construct a campus de novo, they would be more mindful of tensions that might arise due to differences across buildings by income (e.g., market rent with balconies and/or more expensive nishes). To mitigate these tensions and address feelings of "other" sometimes experienced by lower income residents, it is suggested that new campuses engage in proactive planning to minimize the occurrences or need for these differences, provide basic service packages for all residents to engage in joint activities (e.g., congregate dining, excursions), and ensure representation from the various housing components on tenant committees.…”
Section: Campus Design and Functionsmentioning
confidence: 95%
“…Several federal and provincial tax credits also currently exist for caregivers of children and adults with medical conditions and disabilities [43]. However, these nancial aids provide only short-term relief and many caregivers are unaware of their eligibility and do not know how to access these supports [4]. Further, in 2011, the Manitoba government instituted the Caregiver Recognition Act, becoming the rst Canadian province to formally recognize and commit to increased support for caregivers [44] and Nova Scotia recently expanded their Caregiver Bene t Program, to offer eligible recipients providing 20 hours or more of care per week with $400 per month.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Healthcare and growing demands relating to increasing incidence of chronic and often complex conditions have been identi ed by Canadian seniors as important and ongoing concerns affecting their quality of life as they age. So too are concerns around adequate access to information, housing, income security, safety and security, social contacts and networks, transportation (8) in addition to informal caregiving supports and services (9,10) .…”
Section: Introductionmentioning
confidence: 99%